(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
Hypertension is a common cardiovascular disorder, and its pathophysiology differs between humans and pets. This review examines the standard mechanisms by which genetic and environmental risk factors contribute to the development of hypertension in both humans and animals. This study highlights key biological processes, including dysregulation of the renin‒angiotensin‒aldosterone system (RAAS), endothelial injury, oxidative stress, and vascular remodeling. The role of environmental stressors: poor diet, lack of physical activity, and exposure to pollutants, on cardiovascular health in humans and pet animals. This study underscores the global importance of hypertension in both human and animal health and makes a compelling case for a ’One Health’ approach to cardiovascular health. The study’s results highlight the necessity of an integrated, two-species health intervention strategy and reveal a comprehensive, two-way mechanism underlying human-pet health. This study also highlights the importance of common biomarkers (e.g., cortisol and C-reactive protein, or CRP) and diagnostic tools (ambulatory blood pressure monitoring) that can be applied across species to improve hypertension care. This study reveals a novel field of species-specific research that may change the way hypertension is diagnosed, prevented, treated, and managed. Furthermore, additional research will be necessary to fill scientific knowledge gaps and develop advanced medical solutions for treating hypertension, particularly with the investigative potential of comparative genomics and environmental medicine. An interdisciplinary approach in human and veterinary medicine is also necessary to develop efficient, integrated health plans that reduce the risk of cardiovascular disease and to create a more sustainable and effective human-animal model. Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 149-163